The Curse of Kehama, Volume 1 (of 2) - Southey, Robert, 1774-1843 (Salt Lake City, UT : Project Gutenberg, 2017)
"The Curse of Kehama, Volume 1 (of 2)" by Robert Southey is an epic poem published in 1810. Set in a mythological Hindu world, it follows the evil priest Kehama as he sacrifices to gain demonic power and seeks to become a god himself. When peasant Ladurlad kills Kehama's son to protect a girl named Kailyal, the priest unleashes a terrible curse. Yet this curse paradoxically grants Ladurlad extraordinary abilities, allowing him to become an unlikely hero who must ally with Hindu gods to stop Kehama's terrifying ascent. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Curse_of_Kehama
Release date is 2017-08-30
Produced by David Thomas
Keywords: English poetry -- 19th century